(untitled) (Fiep Bulletin - online, 2011)
The aim of this study is to verify that the values transcultural influence satisfaction sport consumption in the context of gyms exclusively for women in Portugal. With a sample of 400 female subjects, we used the theoretical model that depicts the human values of Schwartz (1992), and related indicators of satisfaction with the physical exercise of Villares and Coelho (2005). Through factor analysis identified that benevolence, tradition, conformity and security are most important values to increase satisfaction with the lessons. However, the regressions indicate that compliance has little impact in explaining the satisfaction with other services. We observed a high degree of consumer satisfaction research and intend to continue the service.